Burkitt lymphoma with a granulomatous reaction: an M1/Th1‐polarised microenvironment is associated with controlled growth and spontaneous regression. Issue 2 (5th July 2021) - Granai, Massimo; Lazzi, Stefano; Mancini, Virginia; Akarca, Ayse; Santi, Raffaella; Vergoni, Federica; Sorrentino, Ester; Guazzo, Raffaella; Mundo, Lucia; Cevenini, Gabriele; Tripodo, Claudio; Di Stefano, Gioia; et al.
Abstract : Aims: Burkitt lymphoma (BL) is an aggressive B‐cell lymphoma that, in some instances, may show a granulomatous reaction associated with a favourable prognosis and occasional spontaneous regression. In the present study, we aimed to define the tumour microenvironment (TME) in four such cases, two of which regressed spontaneously. Methods and results: All cases showed aggregates of tumour cells with the typical morphology, molecular cytogenetics and immunophenotype of BL surrounded by a florid epithelioid granulomatous reaction. All four cases were Epstein–Barr virus (EBV)‐positive with type I latency. Investigation of the TME showed similar features in all four cases. The analysis revealed a proinflammatory response triggered by Th1 lymphocytes and M1 polarised macrophages encircling the neoplastic cells with a peculiar topographic distribution. Conclusions: Our data provide an in‐vivo picture of the role that specific immune cell subsets might play during the early phase of BL, which may be capable of maintaining the tumour in a self‐limited state or inducing its regression. These novel results may provide insights into new potential therapeutic avenues in EBV‐positive BL patients in the era of cellular immunotherapy. Abstract :